1991
DOI: 10.2307/3283170
|View full text |Cite
|
Sign up to set email alerts
|

The Lesions and Prevalence of Trypanosoma cruzi in Opossums and Armadillos from Southern Louisiana

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 5 publications
0
28
0
3
Order By: Relevance
“…It is evident that T. cruzi has always been present in Mexico as well as in the United States (Barr et al 1991, Hagar & Rahimtoola 1991, Pung et al 1995, Herwaldt et al 2000, Barnabe et al 2001, the geographic distribution of T. cruzi ranges from the United States to Southern Argentina. According to the information we have compiled about a variety of different topics related to Chagas disease in Mexico, it is clear that we must develop better approaches to understand all of the relevant variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that T. cruzi has always been present in Mexico as well as in the United States (Barr et al 1991, Hagar & Rahimtoola 1991, Pung et al 1995, Herwaldt et al 2000, Barnabe et al 2001, the geographic distribution of T. cruzi ranges from the United States to Southern Argentina. According to the information we have compiled about a variety of different topics related to Chagas disease in Mexico, it is clear that we must develop better approaches to understand all of the relevant variables.…”
Section: Discussionmentioning
confidence: 99%
“…All but 1 of the previous studies on the prevalence of T. cruzi in North American opossums has been conducted by hemoculture (McKeever et al, 1958;Olsen et al, 1964;Barr et al, 1991;Karsten et al, 1992;Pung et al, 1995;Brown et al, 2010). Hemoculture studies have demonstrated that 17 (14%) of 126 opossums from east-central Alabama (Olsen et al, 1964), 88 (16%) of 552 opossums from southwestern Georgia and northwestern Florida (McKeever et al, 1958), 16 (33%) of 48 opossums from Louisiana (Barr et al, 1992), 6 (15%) of 39 opossums from southeast Georgia (Pung et al, 1995), and 1 (8%) of 12 opossums from North Carolina (Karsten et al, 1992) were infected with T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
“…Sera from 30 opossums from southern Louisiana (Barr et al, 1991) were examined in the present study. Frozen samples were sent by overnight carrier from the Department of Clinical Sciences, College of Veterinary Medicine, Cornell University, Ithaca, New York to the Center for Molecular Medicine and Infectious Diseases, Department of Biomedical Sciences and Pathobiology, Virginia Tech, Blacksburg, Virginia (CMMID).…”
Section: Opossum Samplesmentioning
confidence: 99%
“…[3][4][5][6][7][8] Although zoonotic transmission of T. cruzi may be restricted by the absence of appropriate insect vectors in North America, many investigators have speculated that armadillos might be an important source of leprosy infection for humans. 4,9 We wondered if there were any similarities in the epidemiology of these infections among armadillos that could aid our understanding of how the agents are transmitted and benefit our appreciation of their zoonotic potential.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Cross-sectional studies based on point prevalence estimates have only limited value. 10 Studies relating the disease intensity to factors that influence transmission between animals in different areas may be served better by comparing the prevalence of 2 infections or examining the incidence density of the infections.…”
Section: Introductionmentioning
confidence: 99%